Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus terhadap Pertumbuhan Ekonomi di Kabupaten/Kota Provinsi Sumatera Barat Tahun 2016-2019 - Monica Luxsian; Jean Elikal Marna (Universitas Negeri Padang, 2024)
This discussion has the intention of conducting research the effect of original local government revenue, general allocation funds and specific allocation funds in regencies and cities in West Sumatra Province in 2016-2019 using the Panel Regression analysis tool. The model estimation result show that the variables of Regional government revenue, general allocation funds, and specific allocation funds simultaneously or jointly influence economic growth in Districts/Cities of West Sumatra Province in 2016-2019. While partially the economic growth affected by the original local government revenue and General allocation fund .